35‐2: 3D/2D Switchable Display System Based on Integral Imaging. Issue 1 (29th May 2019) - Zhang, Han-Le; Li, Jiao-Jiao; He, Min-Yang; Deng, Huan; Li, Da-Hai; Wang, Qiong-Hua
Abstract : A 3D/2D switchable display system based on integral imaging is proposed by using a projection screen and a projector. The projection screen consists of a lens array holographic optical element (LAHOE) and a polymer dispersed liquid crystal (PDLC) film. The experimental results prove the feasibility of the proposed system.